Hukum dan Kebijakan Energi Terbarukan di Indonesia: Analisis Strategi dan Implementasi - Lubis, Arief Fahmi; Saputra, M. Reza; Khotami, Rizqi Shohibul (DAS Institute, 2025)
This research analyzes strategies and policy innovations in managing natural resources and renewable energy laws in Indonesia. Using a qualitative approach, this study examines the implemented environmental policies, the roles of central and regional governments, and the challenges in their implementation. The results show that Indonesia has implemented various policies and regulations to support sustainable natural resource management. Law No. 32 of 2009 on Environmental Protection and Management is the main foundation, followed by its derivative rules. However, policy implementation still faces challenges such as land conflicts, environmental degradation, and overexploitation of natural resources. In the context of renewable energy, the government has issued fiscal and non-fiscal incentives to promote its adoption. Presidential Regulation No. 112 of 2022 is an example of a policy that provides various tax incentives and licensing facilities for renewable energy projects. This study concludes that Indonesia needs a comprehensive and collaborative approach to address challenges and optimize natural resource management and renewable energy development. Recommendations include simplifying bureaucratic procedures, increasing transparency in procurement processes, and strengthening investment guarantee mechanisms to enhance private sector participation in renewable energy infrastructure development